Disease pattern by upper gastrointestinal endoscopy in rural areas of Tiruchirappalli district carried out at CMCH and RC Irungalur, retrospective study and comparative analysis with other contemporary studies in India - Padma, S.; Murugan, R. (International Surgery Journal, 2018)
Background: Dyspepsia is one of the symptoms of upper Gastro Intestinal diseases which are commonly encountered in clinical practice both in urban and rural areas. The upper gastric intestinal diseases causing dyspeptic symptoms are numerous. The upper GI Endoscopy is one of the essential investigations to evaluate the cause of upper GI tract disease. Retrospective study was done to know the pattern of upper GI tract diseases by upper GI endoscopy in CMCH and RC and compare this study with other studies from south India as well with other regions of India. Methods: Endoscopy data base records of 2198 patients who underwent upper GI endoscopy between September 2014 to August 2016 were taken from Endoscopy Register of Gastroenterology Department at CMCH and RC. Statistical analysis was done based on disease presented and diagnosis. The results were compared with similar published studies in other parts of India. Results: Positive yield was 94%, Male, female distribution was 61.78% and 38.21%. Among the benign lesions, lesions of stomach constituted 52.3%, oesophageal lesions 24.6%, duodenal lesions 7.8%. Of the benign lesion, gastritis constitutes the 44.9%, varices 8.9%, and lax LES with oesophagitis 8.1% were the leading findings in endoscopic diagnosis. Malignancy distribution was stomach 1%, malignancy oesophagus 2.1%. Conclusions: Upper GI lesion was common in males. The incidence of benign lesion was high compared to malignant lesion. Irrespective of the type of population, gastritis was the commonest finding. The incidence of malignant lesion was found little higher in some studies which may require specific studies to understand the causative factors